2013
DOI: 10.1002/ase.1346
|View full text |Cite
|
Sign up to set email alerts
|

Learning anatomy enhances spatial ability

Abstract: Spatial ability is an important factor in learning anatomy. Students with high scores on a mental rotation test (MRT) systematically score higher on anatomy examinations. This study aims to investigate if learning anatomy also oppositely improves the MRT-score. Five hundred first year students of medicine (n = 242, intervention) and educational sciences (n = 258, control) participated in a pretest and posttest MRT, 1 month apart. During this month, the intervention group studied anatomy and the control group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
4
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 34 publications
9
95
4
9
Order By: Relevance
“…The results of this study also demonstrate a correlation between student's level of spatial ability and their success in learning the spatial relationships in neuroanatomy, a result that is supported by previously conducted studies that have reported similar findings (Garg et al, ; Guillot et al, ; Vorstenbosch et al, ). All anatomy knowledge assessment scores were significantly correlated by the participants' level of spatial ability.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study also demonstrate a correlation between student's level of spatial ability and their success in learning the spatial relationships in neuroanatomy, a result that is supported by previously conducted studies that have reported similar findings (Garg et al, ; Guillot et al, ; Vorstenbosch et al, ). All anatomy knowledge assessment scores were significantly correlated by the participants' level of spatial ability.…”
Section: Discussionsupporting
confidence: 90%
“…Anatomy remains an important cornerstone for medical students, as it provides the foundation with which future clinical knowledge will be expounded upon (Sugand et al, ; Johnson et al, ). As an integral part of medical school anatomy courses in the United States, active dissection supplemented with multimedia and imaging technology in the laboratory establishes a learning environment that enhances problem‐solving and spatial reasoning skills needed to interpret imaging in clinical practice (Sugand et al, ; Vorstenbosch et al, ). It also promotes self‐reflection and collaboration required as future clinicians (Lachman and Pawlina, ; Sugand et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Actively encouraging reluctant students to engage in the artistic activity may help them to realise that they can actually learn in different ways (Naug et al, 2011), which is important for their metacognition and lifelong learning beyond anatomy and medical school. While artistic background and learning preferences may not influence learning with artistic methods, it is important to be aware of the existence of gender differences in visuospatial ability (Langlois et al, 2013;Linn & Petersen, 1985), an attribute which in turn is a key indicator of anatomical understanding (Fernandez, Dror, & Smith, 2011;Guillot, Champely, Batier, Thiriet, & Collet, 2007;Rochford, 1985;Vorstenbosch et al, 2013). …”
Section: Tip 6: Know Your Audiencementioning
confidence: 99%